GENDING PENGIRING ABDI DALEM CITRALATA DAN PRALATA DALAM UPACARA GAREBEK DI KERATON YOGYAKARTA - Saptono (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
The research aims to describe the role of gendhing as an accompaniment to Abdi Dalem (court servants) Lurah Citralata and Pralata during ceremonial events at The Sultanate of Yogyakarta in the modern era, specifically during the reign of Sri Sultan Hamengku Bawono ka-10. To date, there has been limited research that specifically estimates this Citralata and Pralata court servants in the context of revitalization, particularly during the Garebek ceremony. The emergence of the Citralata and Pralata court servants has become a notable spectacled for the public especially when witnessed first hand. The event introduces a renewed impression, as Citralata and Pralata court servants had not been featured in the Garebek ceremony for several decades. This study therefore offers valuable insights into the role of Citralata and Pralata court servants within the ceremony. It also explores the gamelan ensemble used, the structure of the gending compositions, their performance, and their cultural meanings. This research employs a qualitative method, focusing on descriptive analysis through literature review and interviews with abdi dalem who were directly involved in the Garebek ceremony. Findings indicate that the gamelan music, drumming patterns, and presentation of gending have undergone reconstruction and changes. In conclusion, whether through reconstruction, revitalization, or transformation, these elements continue to play an essential role in supporting the Garebek ceremony